Recent enhancements to ORM - Halpin, Terry; Curland, Matthew (Springer Berlin Heidelberg, 2013)
Fact-oriented modeling approaches such as Object-Role Modeling (ORM) employ rich graphical notations for capturing business constraints, and validate their data models with domain experts by verbalizing the models in natural language, and by populating the relevant fact types with concrete examples. This paper discusses several recent enhancements to ORM, including the following: further constraints on supertype link roles and their relevance to restricted mandatory role constraints; inclusive-or constraints on roles hosted by different types; refinements to the concept of independent object types; additional kinds of reference schemes and associated uniqueness constraints; and verbalization of further constraint cases involving subtyping, additional reference scheme patterns, uniqueness and frequency constraints involving unaries, and external uniqueness constraints involving n-ary fact types. The paper also includes some discussion of how these enhancements have been supported, or are soon to be supported, in the Natural ORM Architect (NORMA) tool.